PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT JALA LINTAS MEDIA GROUP CABANG BOGOR - Deni Irawan; Andri Priadi (Al Hasanah Barokah Foundation, 2025)
This study aims to analyze the influence of physical work environment and work motivation on employee performance at PT Jala Lintas Media Group Bogor Branch, both partially and simultaneously. The method used is an associative method with saturated sampling technique, involving 70 respondents. Data analysis includes validity, reliability, classical assumptions, linear regression, correlation coefficient, determination coefficient, and hypothesis testing. The results show that the physical work environment has a significant effect on employee performance (Y = 16.201 + 0.588X1) with a correlation of 0.722 and a determination of 52.1% (t count 7.380 > t table 2.009). Work motivation also has a significant effect (Y = 13.145 + 0.662X2) with a correlation of 0.666 and a determination of 44.4% (t count 6.316 > t table 2.009). Simultaneously, the physical work environment and work motivation have a significant effect on employee performance (Y = 7.948 + 0.417X1 + 0.389X2) with a correlation of 0.794 and a coefficient of determination of 63.1%, while 36.9% is influenced by other factors. The F test shows that F count 41.856 > F table 2.790, so H0 is rejected. Thus, both partially and simultaneously, the physical work environment and work motivation have a significant effect on employee performance.